2016
DOI: 10.1111/ane.12557
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body cryostimulation (cryotherapy) provides benefits for fatigue and functional status in multiple sclerosis patients. A case-control study

Abstract: WBC appears to be effective in improving functional status and the feeling of fatigue in patients with MS and especially in those who are the most fatigued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 30 publications
(32 reference statements)
2
51
0
Order By: Relevance
“…The results of the present study is in line with Miller et al [8,] who reported the positive influence of whole body cryostimulation on general fatigue in MS patients with different fatigue levels. However, our results revealed that the decrease in general fatigue among patients in the cooling group (Δ = -6.0, effect size = 2.8) is higher than that reported by Côté et al [28] in PwMS undergoing treatment for sleep disorders (Δ = -3.1, effect size = 0.82).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study is in line with Miller et al [8,] who reported the positive influence of whole body cryostimulation on general fatigue in MS patients with different fatigue levels. However, our results revealed that the decrease in general fatigue among patients in the cooling group (Δ = -6.0, effect size = 2.8) is higher than that reported by Côté et al [28] in PwMS undergoing treatment for sleep disorders (Δ = -3.1, effect size = 0.82).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, different studies have attempted to control patients' body temperature through body cooling using either cool water [6], or cryotherapy [7,8]. One study reported a significant decrease of 0.3-0.7°C in the body temperature of patients with MS (PwMS) using cooling garments [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, combining pharmacological and alternative therapies would be the key toward an optimal management plan. A variety of alternative therapies has been assessed in this setting such as exercise [84], cognitive behavioral therapies [232], cryostimulation [130], and noninvasive brain stimulation (NIBS) [24,152] -and the list goes on. For the sake of this review, we will only focus on NIBS techniques.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Whole-body cryotherapy (WBC) is commonly used as a therapeutic method in rheumatic and inflammatory diseases and in the pain treatment of muscles, joints, soft tissues, and degenerative diseases of muscle spasticity [14]. During WBC, the subject is exposed to extreme cold temperatures for a short period of time.…”
Section: Introductionmentioning
confidence: 99%